2004
DOI: 10.1101/lm.75304
|View full text |Cite
|
Sign up to set email alerts
|

A semi-persistent adult ocular dominance plasticity in visual cortex is stabilized by activated CREB

Abstract: The adult cerebral cortex can adapt to environmental change. Using monocular deprivation as a paradigm, we find that rapid experience-dependent plasticity exists even in the mature primary visual cortex. However, adult cortical plasticity differs from developmental plasticity in two important ways. First, the effect of adult, but not juvenile monocular deprivation is strongly suppressed by administration of barbiturate just prior to recording visual evoked potentials, suggesting that the effect of adult experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
121
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 69 publications
(99 reference statements)
10
121
0
Order By: Relevance
“…However, one unusual feature of mouse ocular dominance plasticity is that it persists well into adulthood (42), particularly when visual experience is enriched (49,50). An additional complication is that the ocular dominance shift initiated in adults reverts spontaneously when binocular vision is restored (51,52) or if both eyelids are closed (53). Thus, for the mouse to serve as a useful model for amblyopia following early-life MD, it was of particular importance to understand the degree to which the juvenile ocular dominance shift persists when binocular experience is restored.…”
Section: Discussionmentioning
confidence: 99%
“…However, one unusual feature of mouse ocular dominance plasticity is that it persists well into adulthood (42), particularly when visual experience is enriched (49,50). An additional complication is that the ocular dominance shift initiated in adults reverts spontaneously when binocular vision is restored (51,52) or if both eyelids are closed (53). Thus, for the mouse to serve as a useful model for amblyopia following early-life MD, it was of particular importance to understand the degree to which the juvenile ocular dominance shift persists when binocular experience is restored.…”
Section: Discussionmentioning
confidence: 99%
“…For example, monocular deprivation shifts the ocular dominance of neurons in the primary visual cortex of adult mice, although the manner of the shift differs from that observed in juveniles (Sawtell et al, 2003;Frenkel and Bear, 2004;Pham et al, 2004). In juvenile mice monocular deprivation causes a rapid reduction of the deprived eye response recorded in the contralateral cortex, followed by a potentiation of the responses driven by the nondeprived eye in the ipsilateral cortex.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, it was reported that the effect of monocular deprivation starts and terminates earlier in layer 4 than in other layers of the cat visual cortex (Daw et al, 1992), and ocular dominance plasticity in layer 4 is much weaker than that in extragranular layers of the mouse visual cortex (Gordon and Stryker, 1996). Furthermore, in layer 2/3 of the cortex, the ocular dominance plasticity remains to a substantial extent in juvenile or even fully mature animals (Daw et al, 1992;Guire et al, 1999;Sawtell et al, 2003;Pham et al, 2004;Sato and Stryker, 2008).…”
Section: Introductionmentioning
confidence: 99%